Trade facilitation and microfinance for poverty reduction in the Greater Mekong Subregion: A case study of Thailand - Kornkarun Cheewatrakoolpong; Sothitorn Mallikamas; Kawin Phupoxsakul (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
This paper investigates whether trade facilitation measures benefit the poor and microenterprises in border provinces. It also explores the role of microfinance in supporting the utilization of the trade facilitation initiatives. The role of microfinance in this context is to complement trade facilitation measures in order to allow the poor to benefit from new market access or business opportunities resulting from trade facilitation measures. The focus of the study is the Economic Corridors and Cross Border Transportation Agreement (CBTA), two important initiatives for transport and trade facilitation under the Greater Mekong Subregion (GMS) programme of the Asian Development Bank (ADB). Thailand has implemented several infrastructure and trade facilitation projects that complement these two GMS initiatives and which are also studied in this paper . These include: (a) The improvement of basic infrastructure around the border locations; (b) Establishment of distribution centres at border locations; (c) Realignment and expansion of roads and highways connected to economic corridors; (d) Construction of customs and immigration control points; (e) Implementation of an e-customs system; (f) Establishment of markets at the border locations; (g) Human resource development. In particular, the trade facilitation measures analysed here are the second and third Thai-Lao Friendship Bridges, the East-West Economic Corridor and related trade facilitation projects. The areas in consideration are within north-eastern Thailand's Mukdahan and Nakhon Phanom provinces.
Keywords: F63; I32; I 38; 330; Trade facilitation; Microfinance; Poverty reduction; The Greater Mekong Subregion; Thailand